Navigating Sustainable School Performance: Integrating Strategic Planning, Innovation Capabilities, and Technology Implementation at XYZ Elementary School - Isnawati Isnawati; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2026)
The Influence of Strategic Planning, Innovation Capabilities, and Technology Adoption on Sustainable School Performance” is a scholarly literature review article in the field of Strategic Management. The purpose of this article is to develop hypotheses regarding the relationships among these variables for use in future research. The research sources include online libraries, Google Scholar, Mendeley, and other academic online media. The research method involves library research using e-books and open-access e-journals. The analysis is qualitative and descriptive. The findings of this article are as follows: 1) Strategic Planning influences Sustainable School Performance; 2) Innovation Capabilities influence Sustainable School Performance; and 3) Technology Adoption influences Sustainable School Performance in elementary schools